2012
DOI: 10.4082/kjfm.2012.33.2.70
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Metabolic Syndrome and Pulmonary Function

Abstract: BackgroundImpaired lung function is associated with mortality rate from cardiovascular and all other death causes. There were previous studies on the relationship between lung function impairment and metabolic syndrome, but they are insufficient. This study was conducted on Koreans to analyze each component of metabolic syndrome as well as its variability between sexes.Methods1,370 subjects underwent a health examination at the Eulji General Hospital Health Center. We examined the association between lung func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Adjustments were made for age, gender, education, smoking status, abdominal obesity, height, hypertension, physical activity, and center. In a Korean study that included 1370 patients aged 20–70 years who had a health examination in 2008, men who had metabolic syndrome had higher mean levels of FEV 1 and FVC than men without metabolic syndrome, and women with metabolic syndrome had higher levels of FEV 1 and FEV 1 /FVC than women without metabolic syndrome . Furthermore, FEV 1 and FVC both declined as a function of the number of metabolic syndrome components in men, but the pattern in women was irregular.…”
Section: Discussionmentioning
confidence: 99%
“…Adjustments were made for age, gender, education, smoking status, abdominal obesity, height, hypertension, physical activity, and center. In a Korean study that included 1370 patients aged 20–70 years who had a health examination in 2008, men who had metabolic syndrome had higher mean levels of FEV 1 and FVC than men without metabolic syndrome, and women with metabolic syndrome had higher levels of FEV 1 and FEV 1 /FVC than women without metabolic syndrome . Furthermore, FEV 1 and FVC both declined as a function of the number of metabolic syndrome components in men, but the pattern in women was irregular.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Recently, research on MetS and pulmonary function has gained momentum worldwide. [14][15][16][17][18] However, to our knowledge, no study involving large-scale populations to assess the relationship between MetS and decreased pulmonary function in non-smoking adults has been conducted. In addition, it is unclear whether the association can be observed in Korean populations.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that MS is related to restrictive, rather than obstructive, pulmonary dysfunction. Others have also shown that MS is associated with a reduction in FVC%pred and FEV1%pred. The restrictive pulmonary dysfunction seen in MS is probably due to the increased WC.…”
Section: Discussionmentioning
confidence: 90%
“…In some studies, it has been reported that poor lung function is seen in those with hypertension, type 2 diabetes, low density lipoprotein cholesterol and abdominal obesity . As the obese population has increased, the incidence of metabolic syndrome (MS) has increased, and there has been a recent report on the relationship between the diagnostic criteria for MS and changes in pulmonary function . But current reference values for lung function are obtained from populations that do not exclude the influence on these values of including individuals with hypertension, diabetes mellitus or obesity .…”
Section: Introductionmentioning
confidence: 99%